Effects of gluteal muscles strengthening on lower-limb injuries in male professional handball players: a preliminary study - Raya-González, J.; García-Esteban, S.; Hume, P.; Castillo, D. (The Journal of Strength and Conditioning Research, 2021)
This study aimed to analyze the effects of a strength training injury-prevention program (STIPP) on injuries associated with weakness of the gluteal muscles in professional handball players. Twenty-seven professional Spanish male handball players from the same club, who competed at the Spanish Second National League level, participated in this study. The investigation was conducted over 2 consecutive seasons (2017-2018 and 2018-2019). The first season served as the control season (n = 21), and the second season served as the experimental season (n = 20). The STIPP was conducted 2 times per week, for 32 weeks, during the in-season period. There were no significant improvements in the injury incidence, pattern, or type for the experimental season group compared with the control season group (injury rate ratio [IRR] = 1.47; 95% confidence interval [CI]: 0.84-2.58; p = 0.17). However, there was a meaningful reduction in the number and burden of lumbar injuries after the STIPP (IRR = 55.83; 95% CI: 0.11-89.01; p = 0.001). In addition, burden values (number of absence days/1000 hours exposure) in all injury pathologies were lower during the experimental season compared with the control season. The STIPP focused on the gluteal muscles could be effective in reducing the number and burden of lumbar injuries in professional handball players.